P3.317 Use of Tablets For Data Collection Among Female Sex Workers: Lessons Learned from a Behavioural Surveillance Study in Honduras, 2012. (13th July 2013) - Farach, N; Galindo, H; Tinajeros, F; Guardado, M
Abstract : Background: The use of tablets and other hand-held devices is increasingly considered as an option for survey data collection, particularly sensitive personal information among key populations. Methods: In 2012, a behavioural surveillance study was conducted among 1426 female sex workers (FSWs) in Honduras. Sensitive personal information was collected, including sexual practises, condom use, sexual violence, alcohol and drug use, and reporting of STI symptoms. Research instruments were inputted into tablets and piloted with FSWs. During the study, facilitators briefed participants in tablet use while participants inputted their responses, in case they had any issues. Daily occurrences were recorded into a log. We analysed qualitative pilot results reports and discussed the advantages and disadvantages of using tablets for data collection with survey facilitators and investigators during regular monitoring visits. Results: Tablet use eliminated the need for paper questionnaires and data entry, and allowed for early database population as surveys were uploaded to a virtual platform. Facilitator help was repeatedly required by participants and self-administered surveys often took more time to complete, particularly during the first sections when participants were familiarising themselves with the tablet. Issues with web connectivity prevented data submission as scheduled in some sites and two tablets were reported missing in one site (out of a total of 22 tablets in the study). Conclusions: The use of tablets can reduce certain study costs (data input, photocopying) and facilitate data management. Facilitators should be available to assist survey participants as they input their own responses, particularly in settings where participants have had little exposure to technology. A brief introduction to tablet use and practise session for participants should be incorporated into the survey flow. Adequate measures should be taken to safeguard tablets and a stable internet connexion should be guaranteed.